The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/2309499019887995
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid in hip fracture surgery: A systematic review and meta-analysis

Abstract: Aims: The primary objective of this review was to determine whether tranexamic acid (TXA) reduces transfusion rates in patients undergoing surgery for hip fractures. The secondary objective was to assess the effects of TXA on mortality and thromboembolic events in the same cohort. Methods: A systematic review of electronic databases was performed in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We included randomized controlled trials comparing perioperative TXA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 23 publications
3
19
0
2
Order By: Relevance
“…It possesses great potential in reducing blood loss and allogeneic blood transfusion safely in patients with hip fractures undergoing surgery. Five meta-analyses [ 116 , 117 , 118 , 119 , 120 ] of RCTs comparing intraoperative administration of TXA with placebo in patients undergoing hip fracture surgery showed significant differences between groups regarding transfusion rates of allogeneic blood, total blood loss, intraoperative blood loss, postoperative blood loss and postoperative haemoglobin, without affecting the rates of thromboembolic events, deep venous thrombosis, acute coronary syndrome, cerebrovascular events, wound complications or mortality.…”
Section: Perioperative Carementioning
confidence: 99%
“…It possesses great potential in reducing blood loss and allogeneic blood transfusion safely in patients with hip fractures undergoing surgery. Five meta-analyses [ 116 , 117 , 118 , 119 , 120 ] of RCTs comparing intraoperative administration of TXA with placebo in patients undergoing hip fracture surgery showed significant differences between groups regarding transfusion rates of allogeneic blood, total blood loss, intraoperative blood loss, postoperative blood loss and postoperative haemoglobin, without affecting the rates of thromboembolic events, deep venous thrombosis, acute coronary syndrome, cerebrovascular events, wound complications or mortality.…”
Section: Perioperative Carementioning
confidence: 99%
“…It possesses great potential in reducing blood loss and allogeneic blood transfusion safely in patients with hip fractures undergoing surgery. 5 meta-analyses [115][116][117][118][119] of RCTs comparing intraoperative administration of TXA with placebo in patients undergoing hip fracture surgery showed significant differences between groups regarding transfusion rates of allogeneic blood, total blood loss, intraoperative blood loss, postoperative blood loss and postoperative haemoglobin, without affecting the rates of thromboembolic events, deep venous thrombosis, acute coronary syndrome, cerebrovascular events, wound complications or mortality.…”
Section: Anemia and Patients Blood Managementmentioning
confidence: 99%
“… 27 Two recent meta-analyses report a significant reduction in blood transfusion using intravenous TXA in patients with HF; however, the heterogeneity is important (I 2 =60%) and the sample size is too small to evaluate the tolerance of this treatment. 28 29 In addition, use of intravenous TXA could be limited in this population of frail patients and topical use of TXA appears to be an effective and safe alternative, at least in major orthopaedic surgery patients. 30–32 It has also been reported that the combined use of intravenous and topical TXA may be superior to intravenous alone in orthopaedic surgery patients.…”
Section: Introductionmentioning
confidence: 99%